Polyurethane Foam as a Novel Material for Ochratoxin A Removal in Tea and Herbal Infusions—A Quantitative Approach - María del Valle Ponce; Mariel Cina; Carlos López; Soledad Cerutti (Foods, 2023)
A novel solid-phase extraction methodology followed by UHPLC-MS/MS has been developed for Ochratoxin A (OTA) analysis in herbal infusions. For this purpose, a commercial polyurethane foam (PUF) was used as sorbent, and the experimental conditions were fully optimized. The strategy was satisfactory for reducing the matrix effect and allowed for OTA quantification in black tea and herbal infusions, with suitable recoveries and quantitation limits in agreement with those required by the maximum levels allowed by current regulations. The achieved results demonstrated the unprecedented use of polyurethane foam as an effective alternative for OTA retention and quantification in herbal infusions with the advantages of simple preparation, time saving, sustainability, and low cost for routine analysis.